Experimental study of the Cu-Al-Sn phase equilibria, close to the copper zone - Soares, Delfim Fernandes; Abreu, Miguel; Barros, Daniel; Castro, Fernando (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The ternary Cu-Al-Sn phase diagram is the base for several important types of alloys, with relevant industrial interest and applications. The knowledge of the melting/solidification alloys characteristics are determinant for their preparation and properties control. However, there is a lack of experimental information on the ternary phase diagram, at high temperature. In this work, several alloys, with high copper content and additions of Al, up to 10%, and Sn, up to 14% (in wt%), were studied by thermal analysis and by isothermal phase equilibria determination. The alloys liquidus and solidus lines and the binary α + β phase field, at 800 °C, are presented for the studied range of compositions.